Exploring the Impact of Reciprocal Teaching Methods on Problem-Solving Skills, Learning Speed, Metacognitive Knowledge, and Academic Self-Concept - Soghra Ebrahimi Ghavam; Mahshid Pourhosein; Mehdi Aslanzadeh (Iranian Journal of Educational Research, 2025)
Objective: The present study investigated the effectiveness of the reciprocal teaching method on problem-solving skills, learning speed, metacognitive knowledge, and academic self-concept of seventh-grade female students in Tehran city. Methods: This semi-experimental study was conducted on a sample of 20 seventh-grade female students in the 9th district of Tehran, selected through a multi-stage cluster sampling method. SPSS version 26 software was used for statistical data analysis, with variance analysis with repeated measurements applied. Results: The test analysis results indicated the positive effect of metacognitive strategies (reciprocal teaching) on students' problem-solving skills, learning speed, metacognitive knowledge, and academic self-concept. Conclusions: Based on these findings, students learn about behavioral, cognitive, and metacognitive strategies during the educational process, which improves their problem-solving skills, learning speed, metacognitive knowledge, and academic self-concept.